2012
DOI: 10.1016/j.ajhg.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

RTTN Mutations Link Primary Cilia Function to Organization of the Human Cerebral Cortex

Abstract: Polymicrogyria is a malformation of the developing cerebral cortex caused by abnormal organization and characterized by many small gyri and fusion of the outer molecular layer. We have identified autosomal-recessive mutations in RTTN, encoding Rotatin, in individuals with bilateral diffuse polymicrogyria from two separate families. Rotatin determines early embryonic axial rotation, as well as anteroposterior and dorsoventral patterning in the mouse. Human Rotatin has recently been identified as a centrosome-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 46 publications
8
75
1
Order By: Relevance
“…Interestingly, an expression study in RTTN mutant fibroblasts showed a significant deregulation of several genes involved in the SHH and WNT pathways, similarly to what we observed in SUFU mutant cells. 56 Taken together, these observations support the finding that polymicrogyria can be part of the spectrum of brain developmental anomalies associated with deregulation of SHH signaling. Besides SUFU p.Ile406Thr, the two affected siblings in family COR369 also shared the homozygous variant p.Thr716Ser in CDHR1.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, an expression study in RTTN mutant fibroblasts showed a significant deregulation of several genes involved in the SHH and WNT pathways, similarly to what we observed in SUFU mutant cells. 56 Taken together, these observations support the finding that polymicrogyria can be part of the spectrum of brain developmental anomalies associated with deregulation of SHH signaling. Besides SUFU p.Ile406Thr, the two affected siblings in family COR369 also shared the homozygous variant p.Thr716Ser in CDHR1.…”
Section: Discussionsupporting
confidence: 76%
“…(Kheradmand Kia et al, 2012). Humans with mutations show an abnormal cortical organization called polymicrogyria, and structural abnormalities of the cilium.…”
Section: Primary Cilia and Cortical Developmentmentioning
confidence: 99%
“…associated with autosomal recessive mutations in GPR56, RTTN (rotatin) and PRICKLE1 (Prickle Planar Cell Polarity Protein 1) genes (see Table 5) [176,227,238,239]. The most severe outcomes of PMG occur in children with severe microcephaly (-3 SD or smaller).…”
Section: 25a Polymicrogyria (Pmg)mentioning
confidence: 99%